Secure Cryptographic Algorithm for a Fault Tolerant model in Unmanned Aerial Vehicles - Sujatha Rajkumar; Ramakrishnan Malaichamy (IAES Indonesia Section, 2014)
AES (Advanced Encryption Standard), provides the highest level of security by utilizing the strongest 128 bit Al-gorithm to encrypt and authenticate the data. AES commercial security algorithm has proved to be effective in Unmanned Aerial vehicles which is used for military purpose such as enemy tracking , environmental monitoring meteorology, map making etc .The demand to protect the sensitive and valuable data transmitted from UAV ( Unmanned Aerial Vehicles ) to ground has increased in Defense and hence the need to use onboard encryption . In order to avoid data corruption due to single even upsets (SEU’s) a novel fault tolerant model of AES is presented which is based on the Hamming error cor-rection code. For this work a problem was chosen that first addresses the encryption of UAV imaging data using the effi-cient AES CBC mode .A detailed analysis of the effect of single even upsets (SEUs) on imaging data during on-board encryption is carried out. The impact of faults in the data oc-curring during transmission to ground due to noisy channels is analyzed .The performance for the above fault tolerant model is measured using power and throughput.